PENCEGAHAN HOAX PERSPEKTIF AL-QUR’AN: Kajian Tafsir Tematik Problematika Kontemporer - Muhammad Yasir (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
The hoax phenomenon has developed in the history of society from the past to the present. This can be caused by various factors of interest, such as in the hadithul ifki incident which happened to the Prophet's wife, Siti Aisyah, who was accused of adultery by hypocrites to divide Muslims at that time. Today, hoaxes are so thick with people's lives because they are easily spread through various social media platforms. Even though the impact felt due to the spread of hoaxes cannot be underestimated. Therefore, in this study it is important to know how to develop society in responding to hoax news. There are two things to be examined, First, what is the Islamic view of hoaxes? Second, what is the solution in the Quran to build an anti-hoax society? The method used in this research is qualitative, the type is library research, and the approach used is normative and sociological theology. While the data collection technique used was heurestics with descriptive data analysis techniques. The purpose of this research is to find out the Qur'anic solution in building society so that it is not easily affected by hoax news. To individuals but also society and state life, every Muslim is obliged to perform tabayyun and maintain his mouth and hands.